Use and Effectiveness of Hypnosis and the Cognitive Interview for Enhancing Eyewitness Recall: Philadelphia, 1988-1989 - Orne, Martin T. ([Verlag nicht ermittelbar], 1991)
This study investigated the effectiveness of hypnosis and the cognitive interview (a technique for stimulating memory) on the recall of events in a criminal incident. The data collected in the study address the following questions: (1) Does hypnosis or the cognitive interview mitigate recall deficits that result from emotionally upsetting events? (2) Does hypnosis or the cognitive interview improve recall when individuals recall events in narrative fashion? (3) Does hypnosis or the cognitive interview improve recall when individuals are required to respond to each item in a set of focused questions? (4) Does the cognitive interview improve recall better than motivated control recall procedures? For this two-stage study, subjects were randomly assigned to receive hypnosis, cognitive interview, or control treatment. Stage 1 involved completing unrelated questionnaires and viewing a short film containing an emotionally upsetting criminal event. Stage 2 was conducted 3 to 13 days later (the average was 6.5 days) and involved baseline information gathering about the events in the film, application of the assigned treatment, and post-treatment written recall of the events. Data were collected from the written narratives provided by subjects and from an oral forced recall of events in a post-experimental interview. Variables in File 1 include total information (correct, incorrect, confabulations, and attributions) as well as new information given in the post-treatment written narrative. The remaining variables in File 1 include score on Harvard Group Scale of Hypnotic Susceptibility, Form A (HGSHS:A), repressor status, and the number of days between viewing the film and completing the baseline and post-treatment interviews. Variables in File 2 were derived from the post-experimental oral forced recall interview and include total correct and incorrect responses and confidence ratings for correct and incorrect responses. The unit of observation is the individual.